Preclinical and translational studies in small ruminants (sheep and goat) as models for osteoporosis research - Dias, Isabel R. (2018)
Purpose of the Review: This review summarizes research on the use of sheep and goats as large animal models of human osteoporosis for preclinical and translational studies. Recent Findings: The most frequent osteoporotic sheep model used is the ovariectomized sheep with 12 months post-operatively or more and the combined treatment of ovariectomized sheep associated to calcium/vitamin D-deficient diet and glucocorticoid applications for 6 months, but other methods are also described, like pinealectomy or hypothalamic-pituitary disconnection in ovariectomized sheep. The goat model for osteoporosis research has been used in a very limited number of studies in osteoporosis research relative to sheep. These osteoporotic small ruminant models are applied for biomaterial research, bone augmentation, efficacy of implant fixation, fragility fracture-healing process improvement, or bone-defect repair studies in the osteopenic or osteoporotic bone. Summary: Sheep are a recognized large animal model for preclinical and translational studies in osteoporosis research and the goat to a lesser extent. Recently, the pathophysiological mechanism underlying induction of osteoporosis in glucocorticoid-treated ovariectomized aged sheep was clarified, being similar to what occurs in postmenopausal women with glucocorticoid-induced osteoporosis. It was also concluded that the receptor activator of NF-κB ligand was stimulated in the late progressive phase of the osteoporosis induced by steroids in sheep. The knowledge of the pathophysiological mechanisms at the cellular and molecular levels of the induction of osteoporosis in small ruminants, if identical to humans, will allow in the future, the use of these animal models with greater confidence in the preclinical and translational studies for osteoporosis research.